Trend in gastric cancer mortality rate in Peru: Segmented regression model 1995 - 2013 - Venegas Ojeda, Diego Rolando (2021)
Objective: To analyze the trends in gastric cancer mortality in Peru from 1995 to 2013 and their differences by sex, age groups, natural regions and political regions. Materials and methods: Ecological time-series study based on 49,690 death records from the Ministry of Health, from 1995 to 2013; Crude, specific and standardized mortality rates (SMR) were calculated by year; according to sex; age group; political and geographic regions, to analyze trends by estimating joinpoints and annual percentage changes (CPA); using segmented regression models, adjusted using Joinpoint Regression Desktop software version 4.5.0.0, Results: The SMR trend due to gastric cancer in Peru was decreasing, falling from 16.1 x 100 000 inhabitants. in 1995 to 11.4 x 100 000 inhabitants. in 2013 (CPA: -2.3), observing decreasing trends by age groups, sex and in 17 of 25 political regions. Differences were found when comparing by subgroups: a more accelerated decrease in women (CPA -2.5) versus men (-2.0) and in age groups (CPA for 75 - 79 years: -2.57 versus CPA for 40 - 44: -1.39); Three geographical areas with high mortality were identified: central Andes (Huancavelica, Huánuco, Ayacucho, Pasco and Junín), northern area (Lambayeque, La Libertad and Cajamarca) and central coast (Ica, Callao, Ancash and Lima), in addition trends were observed growing in Huancavelica, Ayacucho and Pasco. On the coast, mortality has decreased since 1998; however, in the Sierra and Selva it decreases significantly as of 2009. Conclusions: The trend of SMR due to gastric cancer in Peru is decreasing and statistically significant for the period 1995 - 2013 (-2.3% per year). The departments with an increasing trend in mortality are Huancavelica, Ayacucho and Pasco. Greater reduction in SMR is observed in women compared to men.